Dietary Fatty‐Acid Compositions Are more Strongly Reflected in Fatty than Lean Dorsal Fillets of Common Carp (Cyprinus carpio L.). Issue 7 (25th September 2018) - Schultz, Sebastian; Koussoroplis, Apostolos‐Manuel; Kainz, Martin J.
Abstract: In this fish‐feeding study, we tested similarity patterns between fatty acids (FA) in diets and common carp ( Cyprinus carpio ) of fish ponds used for semi‐intensive aquaculture, containing naturally occurring pond zooplankton and different feeds (marine or terrestrial feeds) until carp reached market size. We evaluated if and how total lipid contents in dorsal fillets can reflect dietary FA compositions in farm‐raised common carp and hypothesized that increasing total lipid contents in dorsal fillets significantly increase the similarity between dietary and dorsal fillets' FA compositions. Results of this study showed that carps had higher total lipids when supplied with marine feeds and dietary FA compositions were indeed more strongly reflected in fatty (i.e. high total lipid contents) than in leaner dorsal fillets (low total lipid contents). Increasing total lipid contents in dorsal fillets significantly increased the similarity between the dietary and dorsal fillets' FA compositions. In contrast, leaner dorsal fillets had FA patterns that were more distinct from dietary FA. Total lipid contents higher than 60 mg/g dry weight in dorsal fillets had only limited effects on increasing the similarity between FA compositions of diets and dorsal fillets, and were independent of feed sources. It is thus suggested that higher total lipid contents in dorsal fillets can be used as a proxy to predict dietary FA profiles in common carps, or perhaps even in farm‐raised fish in general.